Chronicles on the Political Economy of Plunder in Ethiopia (1991-2018) - Ayele Gelan (Kindle Direct Publishing, USA, 2018)
ETHIOPIA'S MIRACULOUS ECONOMIC GROWTH THAT NEVER WAS This book brings together twenty five articles that have been written on Ethiopia s current affairs during the country s latest popular unrest (2013-2018). Regardless of the timing of the commentaries, the contents of most pieces reflect circumstances that have prevailed during the reign of the EPRDF (1991-2018). The primarily motive for the writings was to seek answer to the burning issue of Ethiopia s troubled years: what cumulative policy blunders the EPRDF government was making all along to end up with such catastrophic outcomes? Human rights organizations, political activists and opposition parties have done a reasonably good job in scrutinizing and exposing EPRDF s undemocratic governance and gross human right abuses. However, EPRDF s economic policies have always been analyzed in the most unsatisfactory and even bizare ways. In order to fill this gap, economic policy matters were the focus of almost all of the articles contained in this book. The international community was baffled by the popular uprising that errupted in 2015 in Oromia and then spread to all corners of Ethiopia like a forest fire. Until then the prevailing storyline was that Ethiopia was experiencing a miraculous economic growth. But if Ethiopia s economy was really growing at double digit rate per annum for over a decade, then why have Ethiopians in all walks of life protested so vigorously? The existence of draconian press laws meant domestic print and broadcast media were decimated long before the protest years. Personal safety or geopolitical concerns meant foreign correspondents were simply unwilling or unable to even begin to scratch the surface, never mind capturing the nuances of EPRDF s deceptive economic growth rhetoric. There were times when foreign correspondents even resorted to using simplistic indicators, such as high rise buildings in Addis Ababa, to pass judgment on Ethiopians overall economic performance. Dismayed and somewhat frustrated by the gross misinformation regarding EPRDF s economy policies, the author started to write articles and contribute to print and online media to bring some rigor to the debate.